Association of age-dependent height and bone mineral density decline with increased arterial stiffness and rate of fractures in hypertensive individuals. Issue 4 (April 2015) - EL-Bikai, Rana; Tahir, Muhammad R.; Tremblay, Johanne; Joffres, Michel; Šeda, Ondřej; Šedová, Lucie; Awadalla, Philip; Laberge, Claude; Knoppers, Bartha-Maria; Dumas, Pierre; Gaudet, Daniel; Ste-Marie, Louis-Georges; et al.
Abstract : Objective: Hypertension and osteoporosis are age-related health risks differentially expressed in men and women. Here we have analysed their prevalence in a randomly selected cross-sectional cohort [CARTaGENE (CaG) of Quebec, Canada and explored their existing relationships along with height, arterial stiffness and bone fractures. Methods: The principal cohort CaG included 20 007 individuals of age 40–70 years. Participants were subjected to an extensive phenotyping and a questionnaire of medical history and habits. Results: We determined the differences in height of participants and their relation to hypertension status and sex in this cohort and validated it in two other cohorts (The Canadian Heart Health Study and a family cohort from the Saguenay Lac Saint-Jean, a region of Quebec). In all three cohorts, we found that at younger age individuals with hypertension are taller than normotensive individuals, but they have a shorter stature at an older age compared with normotensive individuals. In CaG, we observed that hypertension, low bone mineral density (BMD) and arterial stiffness are strongly associated with height when adjusted for antihypertensive medications ( P  < 0.0001). Fractures are the net outcome of low BMD, and a significant association is observed (odds ratio = 2.34, confidence interval = 2.12–2.57); this relation was stronger in hypertensive individuals compared with normotensive individuals particularly in younger hypertensive individuals. In addition, we observed that increased arterial stiffness was significantly correlated with a low BMD in both men and women at all ages. Conclusion: Shorter stature in elderly, low BMD and fractures correlated with increased arterial stiffness and hypertension. We propose that hypertension and osteoporosis share components of accelerated aging.